THE EFFECTS OF TOTAL ELECTRON CONTENT ON RELATIVE GPS POSITIONING - Arslan, Niyazi (YILDIZ TECHNICAL UNIV, 2010)
Total electron content (TEC) is a parameter that represents ionosphere. Global Positioning System (GPS) positioning is affected from the variations of TEC. Strong geomagnetic storms have an effect on both TEC and GPS observations. One of the period for the severe storm on July 14-17, 2000 (Day of year -DOY- 196199) were chosen to calculate TEC values and North, East and Up coordinate components (n, e, u) for 2h time intervals. TEC values are calculated at ISTA, TUBI and BUCU stations. In the severe storm period, TEC values are decreased from 16 TECU to 3 TECU against its usual day level at 00-02 Universal time (UT) on DOY 198. In addition, n, e and u coordinate components are obtained for 2h time intervals from the three baselines. n, e and u coordinate components are higher in the afternoon hours than the other time interval because of the high TEC.
Keywords: Global positioning system; ionosphere; total electron content; IMPACT; Engineering